PENGARUH PIJAT REFLEKSI KAKI TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI WILAYAH PUSKESMAS ROWOSARI SEMARANG: THE EFFECTS OF MASTER REFLECTIONS ON BLOOD PRESSURE IN THE CLIENTS WITH HYPERTENSION IN REGION PUSKESMAS ROWOSARI SEMARANG - Muhammad Ary Sulaiman; Margiyati Margiyati (JURNAL KEPERAWATAN SISTHANA, 2019)
Hypertension is not infectious disease which occupy the third place in the region’s small-scale Clinics Rowosari Semarang. Less healthy lifestyles as well as stress lead to uncontrolled hypertension and cause various complicatio. Foot reflexiology message is one of complementary therapies with muscle compression techniques giving rise to a relaxing effect and the lower blood pressure. The purpose of this study is illustrate the aplication of reflexiology message theraphy to lower blood preassurein hypertensive clients.The methods used in this research is a descriptive case study method with case study approach. The subject are 2 people with criteria of age 35-65 years old and suffering from hypertension grade I and II. Intervensions carried out in the form of foot reflexiology massage therapy 30-60 minutes for three days a row. The results of the case study shows that there is a decrease of blood preassure 160/90 mmHg 143/83 mmHg be on subject I and subject II 180/100 mmHg to 155/87 mmHg. Foot reflexiology message therapy is recomended as a nursing intervention in the client management of clients with hypertension.